2001
DOI: 10.1007/s11920-001-0073-3
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in research of trauma and personality disorders

Abstract: Although the association between trauma and personality disorders, particularly borderline personality disorder (BPD), has been well established, the etiologic role of trauma in the development of personality disorders has been a topic of debate. Numerous mediation models have been put forth to explain how trauma can serve as a risk factor for the subsequent development of BPD. The symptomatic overlap between the proposed complex post-traumatic stress disorder diagnosis and BPD has fueled research efforts aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
1
0
2
Order By: Relevance
“…Major Depressive Disorder (MDD) or depressive symptoms, which many of the included studies did not adjust for, may explain the strong association observed with external causes of death, as suicidality risk is increased combined with PTSD [ 77 ]. Adjusting for psychiatric disorders in a study investigating PTSD as an exposure is a challenge, as other conditions may also share trauma as a common aetiology [ 78 ]. However, adjusting for these factors may be unnecessary in the possibility that PTSD may precipitate the formation of other psychiatric disorders, leading to subsequent mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Major Depressive Disorder (MDD) or depressive symptoms, which many of the included studies did not adjust for, may explain the strong association observed with external causes of death, as suicidality risk is increased combined with PTSD [ 77 ]. Adjusting for psychiatric disorders in a study investigating PTSD as an exposure is a challenge, as other conditions may also share trauma as a common aetiology [ 78 ]. However, adjusting for these factors may be unnecessary in the possibility that PTSD may precipitate the formation of other psychiatric disorders, leading to subsequent mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Une incidence plus élevée de carences, de négligences et d'abus dont sexuels durant l'enfance des sujets TPL supporte un scénario de développement psychologique compromis (Zanarini et Frankenburg, 1997 ;Van den Bosch et al, 2002 ;Yen et al, 2001 ;Simeon et al, 2003). Ces traumatismes répétés faciliteraient l'éclosion potentielle du TSPT (Breslau et al, 1991).…”
Section: Dissociation Et Trouble De Personnalité Limiteunclassified
“…Il y aurait une association de cause à effet entre abus sexuel et TPL mais aucune relation causale prouvée ni d'association spécifique entre traumatisme et trouble de personnalité (Links et al, 1988 ;Zanarini et al, 1989 ;Paris et al, 1994 ;Timmerman et Emmelkamp, 2001 ;Yen et Shea, 2001 ;Goodman et al, 2003 ;Ball et Links, 2009). Une autre hypothèse sur l'étiologie du TPL réside dans la négligence, la carence par l'absence de soins, moins sensationnaliste ou facile à définir mais encore plus dévastatrice (Simeon et al, 2003).…”
Section: Dissociation Et Trouble De Personnalité Limiteunclassified